Who should have a pre–discharge home assessment visit after a stroke? A qualitative study of occupational therapists' views - Whitehead, Phillip J.; Fellows, Karen Rachael; Sprigg, Nikola; Walker, Marion F.; Drummond, Avril E.R. (SAGE, 2014)
Introduction: The number of patients who have a pre-discharge home assessment visit following a stroke has been reported to vary nationally. The purpose of this research was to explore the factors influencing occupational therapists' decisions to complete such visits.